EFEKTIVITAS PEMBELAJARAN KOOPERATIF MAKE A MATCH DIBANDINGKAN LKS DALAM PENGUASAAN KONSEP AKUNTANSI - Siti Latifah; Sudjarwo Sudjarwo; Pargito Pargito (Jurnal Studi Sosial / Journal of Social Studies, 2015)
This quasi experimental research aimed to know the interactions between learning models and initial abilities. The mean differences of concept masteries and work sheets with initial ability, learning model that is more effective beetwen make a match and students worksheet in improving accounting concept. Technique used was Cluster Sampling Technique. Pre test determined groups of initial abilities, and post test of concept mastery of accounting improvement. The results interactions between learning models and initial abilities indicate 0.002 0.05, h0 is rejected; Mean high initial abilities concept masteries indicate 0,009 0,05 h0 is rejected, midle 0,564 0,05 H0 be accepted, low 0,006 0,05 h0 is rejected. Make a match is more effective. The conclusion improvement of accounting concept mastery with make a match learning is higher for high and low initial ability, while in the work sheet improvement is higher in the middle initial ability.Penelitian quasi eksperimen bertujuan untuk mengetahui interaksi model pembelajaran dengan kemampuan awal; perbedaan mean penguasaan konsep make a match dan LKS dengan kemampuan awal; model pembelajaran yang lebih efektif antara make a match dan LKS dalam meningkatkan penguasaan konsep akuntansi. Pengumpulan data yang digunakan adalah Teknik Cluster Random Sampling. Pre test menentukan kelompok kemampuan awal, post test peningkatan penguasaan konsep. Hasil interaksi antar model pembelajaran kemampuan awal 0,002 0,05, H0 ditolak. Mean penguasaan konsep antar model kemampuan awal tinggi 0,009 0,05 H0 ditolak, sedang 0,564 0,05 H0 diterima, rendah 0,006 0,05 H0 ditolak. Make a match lebih efektif. Disimpulkan tanpa memperhatikan kemampuan awal, peningkatan penguasaan konsep make a match lebih tinggi dari LKS. Memperhatikan kemampuan awal, peningkatan penguasaan konsep make a match lebih tinggi kemampuan tinggi dan rendah, LKS lebih tinggi kemampuan sedang.Kata kunci: lks, make a match, penguasaan konsep